Rus v období smuty očima švédského špiona Zpráva Petra Petreia z roku 1608 - Štěříková, Hana (Karolinum Press, 2021)
This book presents an original historical source, entitled "An erudite and true narration of some changes that recently took place in the Grand Duchy of Moscow," written by the Swedish ambassador to the court in Moscow and first printed in Stockholm in 1608. In his diplomatic report, the author vividly describes the political crisis in the Moscow empire, the tragic events of the Time of Troubles and the plots surrounding the successorship to the tsarist throne which he witnessed. He also depicts events that preceded these events, interpreting them in accordance with the territorial and confessional integrity of the Swedish Kingdom. In addition to the translation of the Swedish original into Czech, the book also contains a philological and historiographical essay, which sets the author's work into the context of Swedish literature and political context at the turn of the 16th century. Thanks to its wide range of interpretive possibilities, the text is suitable material for students of philological and historical disciplines.